THE ORGANIZATION OF ASSESSMENT PROCESS OF NON-FORMAL AND INFORMAL LEARNING ACHIEVEMENTS - Šliogerienė, Jolita (Acta Paedagogica Vilnensia, 2009)
Assessment and recognition of non-formal and informal learning achievements has been widely discussed and some researches have already been done in Lithuania. Talking about the administration of any procedure, the application of procedures and assessment mechanisms for non-formal and informal learning, the transparency of decision making, the competence of the staff evaluating the candidate and personal experience of the experts who are going to do the assessment is expected. Having analyzed the scientific literature as well as some results of the researches carried out in different countries and the experience they have in the validation and accreditation of non-formal and informal learning, the procedure of the assessment and recognition of non-formal and informal learning can be classified into two types: administrative and assessment. Having taken into account the stages, the procedure of the assessment and recognition of non-formal and informal learning according to the functions that should be performed as well as the responsibility of the institution and the individual involved in the process of validation and accreditation, we present the structural elements of the procedure itself. The procedure is presented from the point of view of the functions – the structural elements are analyzed according to the function they perform. Four main elements of the procedure of the assessment and recognition of non-formal and informal learning are defined: administration, monitoring, assessment and audit. According to the systems theory, the existence of each element is essential to have a complete system and to function effectively. The steps that should be taken by the candidate while undergoing through the procedure of assessment and recognition of non-formal and informal learning achievements are described in the article.